Pengolahan Bunga Telang (Clitoria ternatea) Menjadi Sirup di Desa Suka Damai, Kutai Kartanegara sebagai Upaya Meningkatkan Keterampilan Ibu-ibu PKK Suka Damai - Sihaloho, Tulus Pieter Jonathan; Muliati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
This study aims to enhance the skills of PKK mothers in Suka Damai Village, Kutai Kartanegara, in processing butterfly pea flowers (Clitoria ternatea) into an economically valuable product, namely syrup. Butterfly pea flowers, known for their potential as natural colorants and antioxidant sources, are processed into a safe and consumable syrup that can be marketed as a local product. Through training and mentoring activities, PKK mothers were taught how to harvest, process, and package the butterfly pea syrup hygienically. The results showed an improvement in the mothers' skills in transforming raw materials into marketable products, with the potential for increased income through the sale of the syrup. The produced syrup has a unique flavor and appealing color, which could become a flagship product of the village. This training also fostered entrepreneurship among the PKK mothers, which is expected to strengthen both family and village economies.